Soda noteikšanas principi - Želve, Sanda (Latvijas Universitāte, 2007)
Bakalaura darbā ir izpētīts un atklāts soda jēdziens un soda mērķi un vēsturiskā attīstība, kā arī noskaidroti faktori, kas tiek ņemti vēra nosakot personai sodu, analizēta Latvijas Krimināllikuma V. nodaļa par soda noteikšanu, kā arī šīs nodaļas piemērošana tiesu praksē. Tāpat ir aplūkoti soda noteikšanas principi ārvalstu krimināllikumos. Bakalaura darbs sastāv no četrām nodaļām, kas raksturo soda jēdzienu un mērķi, soda noteikšanas vispārīgos un speciālos principus, kā arī soda noteikšanu ārvalstu krimināllikumos.

Punishment is in all societies and in all developments of societies. Criminal law provide criminal liability. Criminam punishment is not vengeance for performing crime. It is instrument for legal procedure. Administration of punishment is functional of government. Indications of punishment 1) compulsory character; 2) punishment is adaptable only for person, who commit a crime; 3)exist possibility to appeal vedict. Pupose of punishment: 1) punish person, who commmit a crime; 2) not to allow new crimes; 3) have influance on society to not allow criminal offenses. Justice heed character of crime, damages, identity of causer, palliatives of liability, status, who deepen liability and special princeples of determanition of the punishment, to pass judgemant. Palliavites of liability give rise to judge determine lesser punishment. Status, who deepen liability, give rise to judge determinē severe punishment. Special princeples of determanition of the punishment regulate determination of the punishment, if exist unusual conditions, like, release on probation.
The principles of the termination the punishment
Keywords: Juridiskā zinātne